2021
DOI: 10.3389/fonc.2021.758512
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical Stem Cell Transplantation for Acute Myeloid Leukemia: Current Therapies, Challenges and Future Prospective

Abstract: Haploidentical stem cell transplantation (haplo-SCT), an alternative donor source, offers a curative therapy for patients with acute myeloid leukemia (AML) who are transplant candidates. Advances in transplantation techniques, such as donor selection, conditioning regimen modification, and graft-versus-host disease prophylaxis, have successfully improved the outcomes of AML patients receiving haplo-SCT and extended the haploidentical transplant indictions for AML. Presently, treating de novo AML, secondary AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 165 publications
(263 reference statements)
0
11
0
Order By: Relevance
“…25 Haplo-HCT is increasingly used in patients with active AML at transplantation. 27 While PTCy is highly efficient at preventing GVHD it also has a strong impact on immune reconstitution after transplantation by rendering alloreactive T-cells functionally impaired. 28,29 It is thus unclear whether observations made by prior studies comparing BM to PBSC on GVL effects outside of the PTCy setting hold true in the PTCy-based Haplo-HCT setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Haplo-HCT is increasingly used in patients with active AML at transplantation. 27 While PTCy is highly efficient at preventing GVHD it also has a strong impact on immune reconstitution after transplantation by rendering alloreactive T-cells functionally impaired. 28,29 It is thus unclear whether observations made by prior studies comparing BM to PBSC on GVL effects outside of the PTCy setting hold true in the PTCy-based Haplo-HCT setting.…”
Section: Discussionmentioning
confidence: 99%
“…Haplo‐HCT is increasingly used in patients with active AML at transplantation 27 . While PTCy is highly efficient at preventing GVHD it also has a strong impact on immune reconstitution after transplantation by rendering alloreactive T‐cells functionally impaired 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to unrelated transplants, we found a remarkable increase in the number of related transplants for patients with AML, which reflected the increasing number of haploidentical transplants. In particular, Chang et al reported that haploidentical allogeneic transplants for AML were the most attractive alternative donors because almost every patient can find a donor in China 20 . Our survey results also reflected this continued growth in transplant activity, in which a significant number of patients with AML were treated with haploidentical transplants in China 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The induction chemotherapy used Cytarabine 100 mg/m 2 and Mitoxantrone 12 mg/m 2 followed by Cytarabine 1000 mg/m 2 for consolidation, and complete remission was achieved with negative measurable residual disease. Due to poor outcome of tAML, he received haploidentical HSCT (haplo‐HSCT) with myeloablative conditioning regimens followed by post‐transplant cyclophosphamide in December 2021 with donor cells from his daughter due to no matched donor available 5 . On post‐HSCT day 30, bone morrow examination revealed engraftment of donor stem cells with full donor chimerism.…”
mentioning
confidence: 99%
“…However, availability of stem cells is time‐consuming and experience is limited. HSCT with haploidentical source, which is easily available, 5 is another option for such a dilemma. We report a rare and successful haplo‐HSCT for tAML after 10 years of auto‐HSCT of Hodgkin lymphoma and suggest the value of haplo‐HSCT in such condition.…”
mentioning
confidence: 99%